Transient neonatal diabetes mellitus with subtype ZFP57 genetic defect in 6q24 - M. Hekal, Abeer; M. Abdel Reheim, Naguib; Yaseen, Hakam; Elsenwi, Ayman (International Journal of Research in Medical Sciences, 2024)
Neonatal diabetes (NDM) is a rare form of diabetes that manifests in the first few months of an infant’s life. The condition affects approximately one in 300,000 to 400,000 newborns and is characterized by elevated blood glucose levels. Transient and permanent NDM are the two types of this disease. In most cases of transient neonatal diabetes mellitus (TNDM), the genetic cause has been attributed to the overexpression of chromosome 6q24. Regardless of its underlying cause, the primary treatment for neonatal diabetes is insulin therapy.